A Longitudinal Functional Magnetic Resonance Imaging Study of Working Memory in Patients Following a Transient Ischemic Attack: A Preliminary Study - Wei Su; Jian Guo; Yun Zhang; Jie Zhou; Ning Chen; Muke Zhou; Rong Li; Huafu Chen; Li He (Neuroscience Bulletin, 2018)

Application of Bacillus velezensis NJAU-Z9 Enhanced Plant Growth Associated with Efficient Rhizospheric Colonization Monitored by qPCR with Primers Designed from the Whole Genome Sequence - Yang Zhang; Xu Gao; Shuai Wang; Chengzhi Zhu; Rong Li; Qirong Shen (Current Microbiology, 2018)

The CAMS Climate System Model and a Basic Evaluation of Its Climatology and Climate Variability Simulation - Xinyao Rong; Jian Li; Haoming Chen; Yufei Xin; Jingzhi Su; Lijuan Hua; Tianjun Zhou; Yanjun Qi; Zhengqiu Zhang; Guo Zhang; Jianduo Li (Journal of Meteorological Research, 2018)

An Assessment of CAMS-CSM in Simulating Land–Atmosphere Heat and Water Exchanges - Guo Zhang; Jianduo Li; Xinyao Rong; Yufei Xin; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua (Journal of Meteorological Research, 2018)

Changes in gene and genotype frequencies during the development of the grass carp Ctenopharyngodon idella - LiB. He; Lv Xiong; AiD. Zhang; YongM. Li; Rong Huang; LanJ. Liao; ZuoY. Zhu; YaP. Wang (Journal of Fish Biology, 2018)
In this study, a full‐sib population of Ctenopharyngodon idella was constructed and approximately 500 C. idella individuals were sampled at four early developmental stages (hatching, first feeding, juvenile fish and young fish). Four DNA pools were constructed and subjected to next‐generation sequencing. On the basis of the identification of single nucleotide polymorphisms (SNP), changes in gene and genotype frequencies during the developmental progress of C. idella were revealed, which indicates that death during the early developmental stage is not a random process. These findings will establish the basis for further studies performed for identifying superior alleles or genotypes as target markers for molecular breeding.

Plant-mediated competition facilitates a phoretic association between a gall mite and a psyllid vector - Jianling Li; Sai Liu; Kun Guo; Fan Zhang; Haili Qiao; Jianmin Chen; Mengke Yang; Xiu Zhu; Rong Xu; Changqing Xu; Jun Chen (Experimental and Applied Acarology, 2018)

Mid–Late Cretaceous igneous activity in South China: the Qianjia example, Hainan Island - Sai-Jun Sun; Li-Peng Zhang; Rong-Qing Zhang; Xing Ding; Hong-Li Zhu; Zhao-Feng Zhang; Wei-Dong Sun (International Geology Review, 2018)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

Synthesis, antitumor evaluation and molecular docking study of a novel podophyllotoxin-lonidamine hybrid - Lei Zhang; Jie Zheng; Ying Rong; Chengli Yang; Li Long; Yingshu Xu; Yongzheng Chen; Jing Wang; Qizheng Yao (Medicinal Chemistry Research, 2018)

Identification and genetic mapping for rht-DM, a dominant dwarfing gene in mutant semi-dwarf maize using QTL-seq approach - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Genes & Genomics, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Hydrological response of biological soil crusts to global warming: A ten‐year simulative study - Xin‐Rong Li; Rong‐Liang Jia; Zhi‐Shan Zhang; Peng Zhang; Rong Hui (Global Change Biology, 2018)
Biological soil crusts across the desert regions play a key role in regional ecological security and ecological health. They are vital biotic components of desert ecosystems that maintain soil stability, fix carbon and nitrogen, influence the establishment of vascular plants, and serve as habitats for a large number of arthropods and microorganisms, as well as influencing soil hydrological processes. Changes in temperature and precipitation are expected to influence the functioning of desert ecosystems by altering biotic components such as the species composition of biological soil crusts. However, it remains unclear how these important components will respond to the prolonged warming and reduced precipitation that is predicted to occur with climate change. To evaluate how the hydrological properties of these biological soil crusts respond to these alterations, we used open‐top chambers over a 10‐year period to simulate warming and reduced precipitation. Infiltration, dew entrapment, and evaporation were measured as surrogates of the hydrological functioning of biological soil crusts. It was found that the ongoing warming coupled with reduced precipitation will more strongly affect moss in crustal communities than lichens and cyanobacteria, which will lead to a direct alteration of the hydrological performance of biological soil crusts. Reductions in moss abundance, surface cover, and biomass resulted in a change in structure and function of crustal communities, decreased dew entrapment, and increased infiltration and evaporation of biological soil crusts in desert ecosystems, which further impacted on the desert soil water balance.

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection - Jinfeng Zhang; Wenjuan Zhao; Rong Fu; Chenglin Fu; Lingxia Wang; Huainian Liu; Shuangcheng Li; Qiming Deng; Shiquan Wang; Jun Zhu; Yueyang Liang; Ping Li; et al. (Functional & Integrative Genomics, 2018)

Preparation and evaluation of decellularized porcine carotid arteries cross-linked by genipin: the preliminary results - Yongquan Gu; Fei Wang; Rong Wang; Jianxin Li; Cong Wang; Liqiang Li; Zeqin Xu; Jian Zhang (Cell and Tissue Banking, 2018)

Srk1 kinase, a SR protein‐specific kinase, is important for sexual reproduction, plant infection and pre‐mRNA processing in Fusarium graminearum - Guanghui Wang; Peng Sun; Ziwen Gong; Lianfeng Gu; Yi Lou; Wenqin Fang; Lianhu Zhang; Li Su; Tao Yang; Baohua Wang; Jie Zhou; Jin‐Rong Xu; et al. (Environmental Microbiology, 2018)
Summary SR protein‐specific kinases (SRPKs) uniquely with a spacer region are important splicing factors from yeast to human. However, little is known about their biological functions in filamentous fungi. Therefore, we characterized a SRPK called SRK1 in wheat scab fungus Fusarium graminearum . Our data showed that Srk1 is required for vegetative growth, sexual reproduction and plant infection, and plays critical roles in pre‐mRNA alternative splicing and gene expression. Remarkably, we found that Srk1 displayed dynamic shuttling between cytoplasm and the nucleus, which is regulated by the divergent spacer domain rather than its kinase activity, suggesting a regulatory mechanism for Srk1. Interestingly, Srk1‐GFP also localized to the septal pores, indicating a possible role of Srk1 unrelated to mRNA processing. Although both K1 and K2 lobes of the kinase domain are essential for Srk1 functions, the K2 but not K1 lobe is responsible for the septal pore localization. Lastly, we established that Srk1 physically interacts with the two SR proteins, FgNpl3 and FgSrp1. Overall, our results indicated that SRK1 regulates fungal development, plant infection and mRNA processing by phosphorylation of other splicing factors including SR proteins, and the spacer domain regulates the functions of Srk1 by modulating its nucleocytoplasmic shuttling.

Regulation of myostatin expression is associated with growth and muscle development in commercial broiler and DMC muscle - Tengfei Dou; Zhengtian Li; Kun Wang; Lixian Liu; Hua Rong; Zhiqiang Xu; Ying Huang; Dahai Gu; Xiaobo Chen; Wenyuan Hu; Jiarong Zhang; Sumei Zhao; et al. (Molecular Biology Reports, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

The environmental characteristics and applications of biochar - Chaosheng Zhang; Li Liu; Meihua Zhao; Hongwei Rong; Ying Xu (Environmental Science and Pollution Research, 2018)

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L. - Lifei Luo; Rong Huang; Aidi Zhang; Cheng Yang; Liangming Chen; Denghui Zhu; Yongming Li; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Functional & Integrative Genomics, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

Effects of probiotic on microfloral structure of live feed used in larval breeding of turbot Scophthalmus maximus - Yan Jiang; Zheng Zhang; Yingeng Wang; Yayun Jing; Meijie Liao; Xiaojun Rong; Bin Li; Guiping Chen; Hesen Zhang (Journal of Oceanology and Limnology, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

Supplementation with turmeric residue increased survival of the Chinese soft-shelled turtle (Pelodiscus sinensis) under high ambient temperatures - Yong Chen; Yi-fan Zhang; Hao-cheng Qian; Jing-liang Wang; Zhe Chen; Jose M. Ordovas; Chao-qiang Lai; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2018)

Cytotoxicity in vitro, cellular uptake, localization and apoptotic mechanism studies induced by ruthenium(II) complex - Jincan Chen; Yao Zhang; Guodong Li; Fa Peng; Xinming Jie; Ji She; Guangzhi Dongye; Zhilin Zou; Shiwen Rong; Lanmei Chen (JBIC Journal of Biological Inorganic Chemistry, 2018)

Continuous application of different organic additives can suppress tomato disease by inducing the healthy rhizospheric microbiota through alterations to the bulk soil microflora - Hongjun Liu; Wu Xiong; Ruifu Zhang; Xinnan Hang; Dongsheng Wang; Rong Li; Qirong Shen (Plant and Soil, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

EZH2 promotes cell proliferation by regulating the expression of RUNX3 in laryngeal carcinoma - Rong Lian; Huimin Ma; Zhiyan Wu; Guozheng Zhang; Lei Jiao; Wenjie Miao; Qianqian Jin; Ruixue Li; Ping Chen; Haixu Shi; Wenfa Yu (Molecular and Cellular Biochemistry, 2018)

Exploration of the formation mechanism and source attribution of ambient ozone in Chongqing with an observation-based model - Rong Su; KeDing Lu; JiaYan Yu; ZhaoFeng Tan; MeiQing Jiang; Jing Li; ShaoDong Xie; YuSheng Wu; LiMin Zeng; ChongZhi Zhai; YuanHang Zhang (Science China Earth Sciences, 2018)

A Small Organic Compound Mimicking the L1 Cell Adhesion Molecule Promotes Functional Recovery after Spinal Cord Injury in Zebrafish - Sudhanshu Sahu; Zhihua Zhang; Rong Li; Junkai Hu; Huifan Shen; Gabriele Loers; Yanqin Shen; Melitta Schachner (Molecular Neurobiology, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

β-Arrestin-1 deficiency ameliorates renal interstitial fibrosis by blocking Wnt1/β-catenin signaling in mice - Huiyan Xu; Quanxin Li; Jiang Liu; Jiaqing Zhu; Liang Li; Ziying Wang; Yan Zhang; Yu Sun; Jinpeng Sun; Rong Wang; Fan Yi (Journal of Molecular Medicine, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)